Experimental Study of Confined Low-, Medium- and High-Strength Concrete Subjected to Concentric Compression - Antonius, Antonius; Imran, Iswandi (ITB Journal Publisher, LPPM ITB, 2012)
An experimental study of 23 low-, medium- and high-strengthconcrete columns is presented in this paper. Square-confined concrete columns without longitudinal reinforcement were designed, and tested under concentric axial compression. The columns were made of concrete with a compressive strength ranging between 30 MPa and 70 MPa. The test parameters in the study are concrete compressive strengths and confining steel properties, i.e. spacing, volumetric ratios and configurations. The effects of these parameters on the strength and ductility of square-confined concrete were evaluated. Of the specimens tested in this study, the columns made with higher-strength concrete produced less strength enhancement and ductility than those with lower-strength concrete. The steel configurations were found to have an important role in governing the strength and ductility of the confined high-strength concrete. Moreover, several models of strength enhancement for confined concrete available in the literature turned out to be quite accurate in predicting the experimental results.